2001
DOI: 10.1016/s1055-3290(06)60182-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV Risk in a Random Sample of Street Youths in San Francisco

Abstract: In a random sample of 203 street youths recruited in the Haight-Ashbury neighborhood of San Francisco, the authors found significant differences between those who reported that they could go home if they wanted to compared to those who perceived that they could not go back home. Those who could not go home were significantly more likely to report having been away from home for more than 3 years, having run away before age 13, having been kicked out of their home, and not being in touch with their parents compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Variables found to be independently associated with a history of illicit drug use included lack of familial contact and increased time on the street. Others have reported associations between lack of familial relationship and high risk behavior in studies of at risk youth in other locations (Clements et al, 1997;Forster et al, 1996;Moon et al, 2001;Morakinyo and Odejide, 2003) and suggested that healthcare providers might identify higher risk youth and children by asking simple questions regarding family support. Those who cannot go back to family should have more targeted intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Variables found to be independently associated with a history of illicit drug use included lack of familial contact and increased time on the street. Others have reported associations between lack of familial relationship and high risk behavior in studies of at risk youth in other locations (Clements et al, 1997;Forster et al, 1996;Moon et al, 2001;Morakinyo and Odejide, 2003) and suggested that healthcare providers might identify higher risk youth and children by asking simple questions regarding family support. Those who cannot go back to family should have more targeted intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Children and youth in street circumstances in Bombay reported in focus group discussions the use of drugs as a mechanism to cope with their daily stresses (Kombarakaran, 2004). The high level of drug use reported by Brazilian youth is comparable to that seen in homeless street youth in San Francisco, where between 80 and 99% of homeless street youth report any lifetime history of illicit drug use (Bousman et al, 2005;Gleghorn, Marx, Vittinghoff, and Katz, 1998;Moon, Binson, Page-Shafer, and Diaz 2001) and up to two-thirds report 'recent' use. Street youth in the U.S. are very different however; not only are they older, but lifetime history of IDU is considerably higher (ranging from 32 to 60%) (Clements, Gleghorn, Garcia, Katz, andMarx, 1997, Moon et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…(Table 1). Overall, median age of participants was 22 years [interquartile range (IQR) 20,25], the majority reported injecting daily (64.5%), was male (69.7%) and most (83.5%) reported not being housed the previous night. The median number of reported years of injecting was four (IQR, 2, 7).…”
Section: Analysesmentioning
confidence: 99%
“…The prevalence of HIV/AIDS is three to nine times higher among persons who are homeless or unstably housed compared with persons with stable and adequate housing, depending upon the population and geographic area studied (Allen et al, 1994;Culhane et al, 2001;Estebanez et al, 2000;Fournier et al, 1996;Paris et al, 1996;Shlay et al, 1996;Torres et al, 1990;Zolopa et al, 1994). For example, disproportionately high rates of HIV risk behaviors and infection are found especially among homeless youth (Bailey et al, 1998;Clatts et al, 1998;Clements et al, 1997;Kral et al, 1997;Moon et al, 2001;Pfeifer and Oliver, 1997;Walters, 1999) and homeless persons who abuse drugs or are mentally ill (Andia et al, 2001;Kilbourne et al, 2002;Klinkenberg et al, 2003;Latkin, 1998;Nyamathi et al, 1997;Smereck and Hockman, 1998;Sohler et al, 2000;Somlai et al, 1998;Susser et al, 1993;Zanis et al, 1997). Other studies have shown that among persons at the highest risk for HIV due to injecting drug use or high risk sex, those without a stable home are significantly more likely than others to become infected over time (Joseph and Roman-Nay, 1990;Popkin et al, 1993;Smereck and Hockman, 1998;Song et al, 2000;Susser et al, 1996).…”
Section: Introductionmentioning
confidence: 99%